Melihat Peta Penyebaran Pasien Covid-19 Dengan Kombinasi QGIS Dan Framework Laravel - Muhammad Fahri (LPPM STT Terpadu Nurul Fikri, 2020)
The local government of Ketapang Regency has difficulty tracking the distribution of covid-19 patients. This difficulty is attributed to the data used in the form of tables and coordinate points. In this study, the authors transformed data tables that are difficult to understand into mapping visualization data so that they can easily see which areas have the most ODP, PDP and Positive. With the increasing epidemic of Covid-19 in Indonesia, local governments must be able to make decisions quickly. One way to be able to support the local government in making decisions on Covid-19 by making a distribution of Covid-19 patients based on coordinate maps that can be accessed by parties who have interests in real time via the website. The method used in this research is digitalisis mapping using 2 applications, QGIS and framework laravel. The results of making the mapping application of Covid-19 patients are very accurate in providing a visual picture of the distribution of Covid-19 patients in an area..